P(0) = 1/6 [ 0 0 0 1 ] M G = 1/6 [ 1 4 1 0 ] G = 1/6 ( 5*P1 + P2 )The curve does not pass through point P1.
P'(0) = 1/6 [ 3*t^2 2*t 1 0 ] M G = 1/6 [ 0 0 1 0 ] M G = 1/6 [ -3 0 3 0 ] G = 1/6 ( -3*P1 + 3*P3 )The tangent of the curve at the beginning of the curve is parallel to the line connecting points P1 and P3. From the above derivation, this is true for any B-spline curve.
P(t) = 1/6 [ (6-t^3)*P1 + t^3*P4 ] = P1 + 1/6 t^3 [ P4 - P1 ]This is a straight line segment starting at point P1 and proceeding one sixth of the way towards point P4.
P'(t) = [ 3t^2 2t 1 0 ] M G P''(t) = [ 6t 2 0 0 ] M G Pa''(1) = [ 6 2 0 0 ] M G = 1/6 [ 0 6 -12 6 ] G = P2 - 2*P3 + P4 Pb''(0) = [ 0 2 0 0 ] M G = 1/6 [ 6 -12 6 0 ] G = P2 - 2*P3 + P4We should also show C1 continuity; this is a procedure similar to the one shown above, only for the first derivatives.